Bacillus Species with Dye-remediation Potential – A Mini Review - Zainab Muhammad Sani (UMYU Journal of Microbiology Research)
Dyes are either natural or synthetic pigments used as colour for different items including textile materials, leather, cosmetics, plastic, paper, printing ink, food, human hair or paintings. The persisting colour and toxic compounds contained in most dyes leads to serious environmental pollution which is unsuitable for the survival of many ecologically important organisms. A wide range of bacterial species have been reported to effectively remediate dyes of various types and classes. This paper reviews bacterial species from the genus Bacillus with the potentiality to remediate synthetic dyes based on published literatures. Bacillus species remediate dyes basically through biosorption and enzymatic active. The most commonly used Bacillus species are Bacillus subtilis, B. cereus, B. megaterium, B. fusiformis, B. odysseyi, B. mycoides, B. paramycoides, B. pseudomycoides, B. flexus, B. cohnii, B. licheniformis, B. spizizenii, B. algicola, B. vallismortis, B. vietnamensis, B. stratosphericus, B. halodurans, B. albus, B. aryabhattai and B. velezensis. Other researches have also proven that mixed cultures of Bacillus species and species from other microbial genera display significant efficiency in the remediation of various dyes. These species produce enzymes and compounds that aid in the breakdown of dyes, thus, reducing their impact to the environment. The use of the aforementioned Bacillus species in the remediation of other dye related environmental pollutants is highly recommended.